The AI City - WU, Siegfried Zhiqiang; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2025)
This open access book presents the concept of AI Cites for the first time. It includes the theoretical basis, development frontier, and different application scenarios of artificial intelligence cities. The book is accompanied by rich practical cases to conduct in-depth and detailed discussions on the proposition of artificial intelligence cities. It fills the gap between artificial intelligence and urban planning. This book points out the urgent human needs in the city for AI scientists to considered in the next round of AI technology development. It also provides new ideas for urban planners and researchers to solve problems with new technologies. .
The Development of Smart Cities -- Beyond Smart Cities: AI City Have Arrived -- The Prototype of AI City -- The Determinants of AI City -- The Main Goal of AI City Is The Needs of Urban People -- AI City Technologies -- The Domain of AI City Application -- Organization of AI City -- Global Practice of AI City -- Case: Qingdao Sino-German Eco Park -- Case: Maqiao, Shanghai -- Opportunities and Challenges of Building AI City -- Conclusion: The Emergence of Next Generation AI Technology.
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, described non-text content (images, graphs), bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Architecture; Artificial intelligence; Urban economics; Cities, Countries, Regions; Artificial Intelligence; Urban Economics